Reasons, Years and Frequency of Yoga Practice: Effect on Emotion Response Reactivity - Mocanu, Elisabeth; Mohr, Christine; Pouyan, Niloufar; Thuillard, Simon; Dan-Glauser, Elise S. (Frontiers in Human Neuroscience, 2018)
Yoga practice, even in the short term, is supposed to enhance wellbeing and counteract psychopathology through modification of emotion reactivity. Yoga teaches that emotional responses may be less pronounced with longer and more frequent practice, and potentially when people perform yoga for mental rather than physical reasons. We tested 36 yoga practitioners of varying experience (between 6 months and 11 years of practice). We assessed participants’ self-reported emotional experience and peripheral physiological reactions (heart rate, skin conductance, respiration) when seeing positive and negative pictures. Results were analysed as a function of the years of, frequency for, and reasons of yoga practice. We found a heart rate increase with the degree participants performed yoga for mental reasons. In addition, years of yoga practice were significantly associated with reduced abdominal respiratory rate when facing negative pictures, speaking in favour of reduced arousal with yoga experience. Finally, regarding frequency of practice, a higher frequency in the last month was linked to less negative and positive experiences as well as a reduced abdominal respiratory amplitude when viewing positive pictures. Altogether, these results demonstrate that intense short-term yoga practice might relate to a i) decrease in the intensity of self-reported emotional experiences and ii) deepened respiration. Short-term effects might be shaped by what participants expect as practice benefits. However, several years of practice might be needed to decrease respiratory arousal in the face of negative situations, which likely is a manifestation of an evolution in the emotion regulation process.